Ekstrak Buah Delima Terstandar Menurunkan Derajat Fibrosis Hati pada Hewan Model Tikus Putih (STANDARDIZED POMEGRANATE FRUIT EXTRACT REDUCES LIVER FIBROSIS DEGREE ON ALBINO RATS (RATTUS NORVEGICUS) AS AN ANIMAL MODEL) - Yuniarti, Wiwik Misaco; Handajani, Retno; Kusumobroto, Hernomo Ontoseno; Sudiana, Ketut (Jurnal Veteriner, 2013)
The objective of this study was to analyse the effect of standadized pomegranate fruit extracton liver fibrosis due to biliary obstruction.  Liver fibrosis was induced with bile duct ligation (BDL)technique.  Examinations were performed on the expressions of collagen type 1 and the degree ofliver fibrosis. Thirty two male albino rats (Rattus norvegicus), 2.5 month old, weighing 160-190grams were divided into four experimental groups.  The first group (P0) consisted of rats  whichunderwent laparotomy and treated with 2 ml of  carboxymethyl cellulose (CMC) 0.3%.  Three othergroups consisted of rats which underwent laparotomy and bile duct ligation (BDL) but receiveddifferent treatments.  Group P1 was given carboxymethyl cellulose (CMC) 0.3%, P2 was treatedwith standardized pomegranate fruit extract 150 mg/kgBW/po/day within CMC 0.3% , and P3 wasgiven ellagic acid (EA) 60 mg/kgBW/po/day of equal volume.  Treatments were administered on thesecond day after BDL for 21 days.  The livers were excised one day after the last administration.Observations were made on the expressions of collagen type 1 and the degree of liver fibrosis. Theresults showed that standardized pomegranate extract can inhibit the expression of collagen type Isignificantly in the P2 and P3 compared with P1 group (p <0.05). Treatment with standardizedpomegranate fruit extract also significantly suppressed the progression of liver fibrosis comparedto P1, eventhough there was more liver fibrosis compared to P0 (p<0,05).  The degree of liverfibrosis was not significantly different between P2 and P3, and between P3 and P1 (p>0,05).The administration of standardized pomegranate fruit extract 150 mg/kgBW/po/day  exertedantifibrotic effect by inhibiting the increase the expression of collagen type I and the degree of liverfibrosis.
Keywords: pomegranate fruit, collagen type I, degree of liver fibrosis